Performance of Bituminous Mix based on Aggregate Packing - Mohd Hosni, Mohammad Nurhafizi (Universiti Teknologi Petronas, 2008)
Aggregate dominate 90% of mix structure and its interlocking forces is a key to the strength of the bituminous mix. Realizing that aggregate interlocking contribute to the strength, the packing of aggregate would increase the force of intact between aggregate. The packing density represents how well the aggregate can be pack together. Therefore, combination between various aggregate sizes which yield a highest density is the aim. By assimilating both resource and concept, the idea of aggregate packing concept is developed. Further on the report, the well graded aggregate (control) were not necessarily lead to high density. The concept that fully utilizing density and aggregate as main structure of the bituminous mix, results in high performance with low cost of material.